(untitled) (Research, Society and Development, 2021)
On properties that are used for the agricultural sector, including livestock as one of the main economic bases in the country, it is necessary to have control over activities, especially with regard to productive sustainability. In this sense, sustainability can be assessed through some methodologies that quantify and analyze the property in its set of actions. In this context, the present paper aimed to evaluate two properties with production of beef cattle with different levels of technologies associated with production, using the APOIA-SOCIAL tool, developed by Embrapa, in semi-intensive properties available in Araçatuba/SP and extensive in Ribas do Rio Pardo/MS. The methodology adopted to verify the sustainability in relation to the properties, has the principle of evaluating a set of indicators in economic aspects, employment, management/administration and health. Each factor has its importance in terms of sustainability, bringing balance to the production system. Through the results, it was possible to identify that property 1 (semi-intensive system) has a higher general sustainable index compared to property 2, with superiority in all social aspects, including health, service quality, management by the employer and monitoring of the same and return in relation to the investment and work demanded in the property. It is concluded that, in addition to being an important sustainability assessment tool, not always a cost reduction, as in the extensive system, it recommends a potentially sustainable environment, especially if the producer wants certification processes to explore new markets.